Edukasi Masyarakat tentang Bahaya Merokok di Dalam Rumah sebagai Upaya Perlindungan Kesehatan Keluarga - Aisya Herfatma; Alde Luthfi Afaf; Ananda Gilang Pratama; Nurma Wira Ayu; Salwa; Selvira Puspita Illahi; Vivi Ramadani; Zulfa Maisa Fitri; Gusni Rahma; Afzahul Rahmi; Oktri Warman (Universitas Alifah Padang, 2025)
Threaten the health of residents, especially children, the elderly, and women. Cigarette smoke contains thousands of harmful substances, including carcinogens, which can cause respiratory problems, heart disease, and increase the risk of cancer. Exposure to cigarette smoke in enclosed spaces, including thirdhand smoke that sticks to furniture and clothing, can have long-term health impacts. Therefore, educational efforts are needed to raise public awareness about the importance of smoke-free homes. This community service activity was carried out in July 2025 in Jorong Aro, involving 20 community members. The methods used included door-to-door outreach and leaflet distribution. The activity stages included preparation, implementation, and evaluation. The evaluation results showed an increase in knowledge in the good category from 65.0% before the outreach to 93.5% after the outreach. In addition, the community's positive attitude towards efforts to not smoke indoors increased from 55% to 65%. Based on these results, it can be concluded that the outreach activity was effective in increasing public knowledge and awareness about the dangers of smoking indoors. This activity is expected to encourage the implementation of clean and healthy living behavior by creating a sustainable smoke-free home environment.